2022
DOI: 10.21203/rs.3.rs-1662992/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combination effect of smoking conditions and Dunaliella salina as natural antioxidant on biochemical characters of stored Sander lucioperca fillets

Abstract: Sander lucioperca is a fresh water fish characterized with its remarkable nutritional value. Thus, smoking improves sensory and microbiological characteristics. Therefore smoking processes is associated to alterations in some physicochemical fish properties. The object of this study is to evaluate the combined effects of two different processes of smoking (cold and hot) and natural antioxidants obtained from the microalgea Dunaliella salina administrated at two graded concentrations (+0.5pp and +1pp) on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Messina et al (2019, 2021) also showed that cold smoking combined with antioxidants had a positive effect on lipid peroxidation of meager ( Argyrosomus regius ) fillets, lower values of malondialdehyde, and protected omega‐3 in fish during the process. Moreover, as in the case of Sander lucioperca filets, a fatty fish species, the lipid oxidation results showed that the combined application of Dunaliella salina as natural antioxidant and smoking significantly reduced the oxidation in Sander lucioperca in comparison with the batch that was only smoked (Bouriga et al, 2022).…”
Section: Resultsmentioning
confidence: 98%
“…Messina et al (2019, 2021) also showed that cold smoking combined with antioxidants had a positive effect on lipid peroxidation of meager ( Argyrosomus regius ) fillets, lower values of malondialdehyde, and protected omega‐3 in fish during the process. Moreover, as in the case of Sander lucioperca filets, a fatty fish species, the lipid oxidation results showed that the combined application of Dunaliella salina as natural antioxidant and smoking significantly reduced the oxidation in Sander lucioperca in comparison with the batch that was only smoked (Bouriga et al, 2022).…”
Section: Resultsmentioning
confidence: 98%